2021
DOI: 10.1038/s41392-021-00629-w
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between HLA-G and NK cell receptor KIR2DL4 orchestrates HER2-positive breast cancer resistance to trastuzumab

Abstract: Despite the successful use of the humanized monoclonal antibody trastuzumab (Herceptin) in the clinical treatment of human epidermal growth factor receptor 2 (HER2)-overexpressing breast cancer, the frequently occurring drug resistance remains to be overcome. The regulatory mechanisms of trastuzumab-elicited immune response in the tumor microenvironment remain largely uncharacterized. Here, we found that the nonclassical histocompatibility antigen HLA-G desensitizes breast cancer cells to trastuzumab by bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Unless engaged by HLA-G, KIR2DL4 promotes ADCC and forms a regulatory circuit with the IFN-g production pathway, in which IFN-g upregulates KIR2DL4 via JAK2/STAT1 signaling, and then KIR2DL4 synergizes with the Fcg receptor to increase IFN-g secretion by NK cells. The effect of blocking the HLA-G/KIR2DL4 interaction improves the vulnerability of HER2-positive BC to trastuzumab treatment in vivo [35].…”
Section: Blocking Inhibitory Signals Of Nk Cellsmentioning
confidence: 99%
“…Unless engaged by HLA-G, KIR2DL4 promotes ADCC and forms a regulatory circuit with the IFN-g production pathway, in which IFN-g upregulates KIR2DL4 via JAK2/STAT1 signaling, and then KIR2DL4 synergizes with the Fcg receptor to increase IFN-g secretion by NK cells. The effect of blocking the HLA-G/KIR2DL4 interaction improves the vulnerability of HER2-positive BC to trastuzumab treatment in vivo [35].…”
Section: Blocking Inhibitory Signals Of Nk Cellsmentioning
confidence: 99%
“…Our recent study found that KIR2DL4 synergizes with FcRg to enhance NK cell activation and degranulation, while HLA-G binding to KIR2DL4 impairs the cytotoxicity of NK cells in HER2 positive breast cancer microenvironment (7). These findings suggested that KIR2DL4 might provide a switch for NK cell activity via its association with HLA-G. Increasing evidence has showed that HLA-G is involved in both innate and adaptive immune responses required for immune escape.…”
Section: Introductionmentioning
confidence: 92%
“…Killer cell immunoglobulin-like receptor 2DL4 (KIR2DL4) is the only KIR receptor recognized by HLA-G. KIR2DL4 belongs to the killer cell Ig-like receptors (KIR) family, which is expressed mainly on NK cells (7). KIRs can recognize both classical and nonclassical HLA Class I molecules.…”
Section: Molecular Structure Of Hla-g and Kir2dl4mentioning
confidence: 99%
See 2 more Smart Citations